A study to evaluate the analgesic activity of Origanum vulgare in mice using hot plate method - Raveendran, Siddhi; Tilak, A. V.; Yadav, Shraddha; Das, Sayan; Madrewar, Vishwadeep; Kulkarni, Vishwanath (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The International Association for Study of pain, has defined pain as actual or potential tissue damage or described in terms of such damage. But the burden of unwanted side effects with current regimens are high. To explore the potential of Ayurveda drugs, this study is done by using Origanum vulgare. Methods: In vivo model used-Hot plate method. Origanum vulgare (84 mg/kg p.o) was administered in mice. The analgesic activity was studied by recording the reaction time after administration of the drug at frequent intervals up to 3 hrs. The results were analysed by ANOVA and Tukey’s test. P value <0.05 was considered as significant. Pentazocine showed statistically prolongation in the reaction time after 30 min as compared to Origanum vulgare. Results: In hot plate method, pentazocine showed statistically significant increase in the reaction time after 30 min of administration as compared to control group. However, Origanum vulgare in a dose of 84 mg/kg showed significantly increase in the reaction time after 30 min of administration as compared to control group. On comparing pentazocine and Origanum vulgare, pentazocine showed highly significant increase in the reaction time after 30 min as compared to Origanum vulgare at 84 mg/kg dose. Conclusions: From the present study, it was concluded that extract of Origanum vulgare exerted analgesic activity in both the models. However, it was less potent than pentazocine. Thus, Origanum vulgare can be used in mild to moderate painful conditions.